Moral injury and the priesthood of all believers1. Issue 2 (19th June 2018) - Childs, James M.
Abstract: This article proceeds from the conviction that moral injury suffered by many combat veterans is a deeply spiritual matter requiring spiritual resources for healing. The tradition of the care of souls commends itself. It takes into account that the "soul" is an expression of the whole person in all its physical, spiritual, and social realities. Moral injury affects all those dimensions of personhood or soul. Since the Reformation the care of souls has been a vocation for the ministry of the whole people of God under the theology of the priesthood of all believers. A caring community is essential to healing for many dealing with moral injury. Indeed, the veterans themselves, in sharing their stories and their pain, become part of that ministry of the priesthood of all believers and may well find healing in the meaningfulness of their mutual ministry.